Enhancing the Students Writing Interest Through Case Building Technique - Nur Fitri S (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2018)
This study focused in finding out the degree of students’ interest toward the use of Case Building Technique which its use was limited in writing skill enhancement. The study was a descriptive qualitative. The population of the study was 160 students of English Education Program, Language and Literature Faculty, State University of Makassar in 2012-2013 academic years. Cluster random sampling was used in this study and, due to the large number of population. The researcher chose the classes randomly by using lot. Questionnaire was used as instrument of the research by applying Likert Scale. In collecting data, the researcher distributed the instrument after the implementation of Case Building Technique. The findings revealed 37,5 % of students were strongly interested, 57,5% of students were interested and only 5% of students were moderate. In other words, most students were interested in learning to write English composition by using Case Building Technique. This technique had been found alluring by the students and, therefore, has changed the students’ attitude towards writing.